Respostas
respondido por:
0
Fórmula: an = a1 + (n - 1).r
an = 58
a1 = ?
n = 20
r = 3
58 = a1 + (20 - 1).3
58 = a1 + 19.3
58 = a1 + 57
58 - 57 = a1
a1 = 1
an = 58
a1 = ?
n = 20
r = 3
58 = a1 + (20 - 1).3
58 = a1 + 19.3
58 = a1 + 57
58 - 57 = a1
a1 = 1
respondido por:
0
an
= a1 + ( n -1) . r
58 = a1 + ( 20 -1) . 3
58 = a1 + 57
58 - 57 = a1
a1 = 1
58 = a1 + ( 20 -1) . 3
58 = a1 + 57
58 - 57 = a1
a1 = 1
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás